VIth International Congress on Thrombosis and Haemostasis 1977
DOI: 10.1055/s-0039-1682778
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sialic Acid in the Dysfibrinogenemia Associated with Liver Disease

Abstract: We have described an abnormal fibrinogen in 6 patients with liver disease who had prolonged plasma thrombin times due to impaired fibrin monomer aggregation. To investigate the role of sialic acid in this functional abnormality, fibrinogen was purified from normal and patient plasmas by the glycine precipitation method. Sialic acid content of the fibrinogens was measured by the thriobarbituric acid assay after acid hydrolysis. Normal fibrinogen had 6.1 ± 0.5 residues per molecule of fibrinogen, whereas patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…119,121 Compared to controls, both plasma clots and clots made from purified fibrinogen from cirrhotic patients demonstrate abnormal clotting characteristics, including decreased clot permeability and shorter clot lysis times. 119 Somewhat paradoxically, patients included in this study 119 reported bleeding, mostly variceal, rather than thrombosis.…”
Section: Abnormal Fibrinogen and Fibrin Structure In Thrombosismentioning
confidence: 99%
“…119,121 Compared to controls, both plasma clots and clots made from purified fibrinogen from cirrhotic patients demonstrate abnormal clotting characteristics, including decreased clot permeability and shorter clot lysis times. 119 Somewhat paradoxically, patients included in this study 119 reported bleeding, mostly variceal, rather than thrombosis.…”
Section: Abnormal Fibrinogen and Fibrin Structure In Thrombosismentioning
confidence: 99%
“…In addition, specific thrombin clotting times were prolonged in newborns suggesting differences in polymerization of fibrin from 'fetal' fibrinogen [8], an observation that has led to a claim that fibrinogen in infants is 'dysfunctional' [9]. Observations that an increase in sialic acid content of fibrinogen is associated with a decreased rate of fibrin polymerization and the removal of sialic acid residues leads to increase in polymerization [10] provide a possible explanation for the differences in thrombin clotting times. Definite evidence of the importance of differences in sialic acid content of fibrinogen is provided by observations that sialic residues of fibrinogen directly bind Ca 2þ [11].…”
Section: Introductionmentioning
confidence: 99%
“…Dysfibrinogenaemia, where the function of the fibrinogen is impaired, is also one of the earliest clotting abnormalities seen in chronic liver disease 35. These defective forms of fibrinogen may be synthesised because of abnormal post-translational modification or excessive sialic acid content 36 37…”
Section: The “Other Factors” In Haemostatic Dysfunctionmentioning
confidence: 99%